2005
DOI: 10.1111/j.1538-7836.2005.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Pro475Ser polymorphism in ADAMTS‐13 in Caucasians

Abstract: To cite this article: Bongers TN, de Maat MPM, Dippel DWJ, Uitterlinden AG, Leebeek FWG. Absence of Pro475Ser polymorphism in ADAMTS-13 in Caucasians. J Thromb Haemost 2005; 3: 805.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…22 Plaimauer et al expressed several constructs of recombinant For personal use only. on May 9, 2018. by guest www.bloodjournal.org From ADAMTS13 and observed that both the A732V and P618A polymorphisms reduced secretion (60% and 27%, respectively) and activity (72% and 14%, respectively) in comparison with WT.…”
Section: Discussionmentioning
confidence: 99%
“…22 Plaimauer et al expressed several constructs of recombinant For personal use only. on May 9, 2018. by guest www.bloodjournal.org From ADAMTS13 and observed that both the A732V and P618A polymorphisms reduced secretion (60% and 27%, respectively) and activity (72% and 14%, respectively) in comparison with WT.…”
Section: Discussionmentioning
confidence: 99%
“…A number of nonsynonymous mutations and polymorphisms of ADAMTS13 have been identified [4,5]. Among them, the P475S (c.1423C > T) polymorphism is noteworthy.The allele frequency of ADAMTS13 P475S was 5.1% in Japanese subjects [6], 4.0% in Koreans [7], and 1.5% in Chinese [8], but absent in Caucasians [9]. The recombinant P475S mutant was normally secreted from cultured cells but showed greatly reduced enzymatic activity (10%) in the VWFmultimer assay [6].…”
mentioning
confidence: 99%
“…However, in these studies only AA-induced PA was used to explore aspirin resistance. No direct measure of platelet TxA 2 , considered a prerequisite to analyze the rate of COX1 and eventually aspirin resistance, was provided [9]. Here, we undertook a prospective study to further evaluate the role of compliance on aspirin resistance intended as residual platelet reactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the proline (Pro) to serine (Ser) polymorphism in codon 475 of the ADAMTS13 gene (Pro475Ser), caused by a base substitution of C1423 to T in exon 12 (C1423T) which was found to impair ADAMTS-13 activity in vitro , has been reported to be common in the Japanese population, and suggested that the importance of TTP or thrombosis-related gene in Japanese 10. However, subsequent studies carried out in the Chinese population13 or Caucasians14 did not show positive correlation of C1423T with thrombotic disorders. The allele frequency of C1423T was only 1.5% in the Chinese population, and the heterozygous genotype was not associated with an increased risk of acute ischemic stroke and acute myocardial infarction 13.…”
Section: Introductionmentioning
confidence: 99%